Ibn Rušd's Influence on the Philosophical Life of the West on the Eve of the Renaissance - Saeed Mahmudpoor; Habibollah Danesh Shahraki; Sayyed Ahmad Fazeli (آموزه‌‌های فلسفه اسلامي)
On the eve of passing through the scholasticism, we encounter a period of transition called the Renaissance. Although less attention has been paid to this historical period in the philosophical life of the West, but the role of Muslim philosophers, especially Ibn Sina (Avicenna) and Ibn Rushd (Latinized Averroes), has played an important and influential role in the philosophical thought of this period. The influence of Muslim philosophers on the philosophical life of the West has been done through the translations and interpretations of philosophers and school teachers. As a result, misconceptions have sometimes occurred. An example of these misconceptions can clearly be found in the meanings of double reality. In this article, we analyze the meanings of double reality (doubling in action, cognition, discourse, fact in itself; thing in itself) and examine three Latin Ibn Rushdians who had a greater impact on the intellectual space of their time. Then we will examine the consequences of the Latin Ibn Rushdian on the eve of the Renaissance.